# So i just realized that i asked the same question. pooey. Help!

Ahh yes our entire angle = 90° lets remember that.
and we need to find out what x is.
all we do is plug in both of our values and make it all equal 90 degrees
just like an equation:)
here ill show you
m∠1 = (x + 33°)
m∠2 = 2x°
and we know that
m∠1 + m∠2 = 90°
so lets plug in what we have

(x + 33°) + 2x° = 90°

1st. subtract 33° from both sides
(x + 33°) + 2x° = 90°
- 33°            = -33° cancels out on the left side, right side we solve it:)
90° - 33° = 57° now lets rewrite this
x + 2x° = 57°

x + 2x° = 57° becomessss
3x° = 57°

3rd. we divide both sides by 3
3x° = 57°
÷3  = ÷ 3 the left side cancels out and we solve the left side
x = 19°

FINALLY! now  we arent finished yet! lets plug in our x value to get our 2 angle measures
we know that
m∠1 = (x + 33°)
so lets plug in 19° for x
m∠1 = 19° + 33°  SOLVE!
m∠1 = 52°

wait! lets find what m∠2 equals
m∠2 = 2x°
so lets plug in 19° for x
m∠2 = 2(19) lets solve:)
2 x 19 = 38
sooooo
m∠2 = 38°

m∠1 = 52°
M∠2 = 38°

have a good day ma'm
and dont forget 2
MARK ME BRAINLIEST!
=)

So we know the angle is 90 degrees, now we set it up: (X+33)+2x=90. Now solve: 3x+33=90. 3x=57. X=19. Now we sub it in: angle 1=19+33=52. Angle 2=2x19=38. Check it 38+52=90 :)